Korea Gerontol Soc 2022
DOI: 10.31888/jkgs.2022.42.4.787
|View full text |Cite
|
Sign up to set email alerts
|

노인의 퇴원 후 전환기 돌봄서비스 필요도에 대한 예측요인

Abstract: Chronic diseases in the growing elderly population lead to repeated hospitalizations and consequent deterioration of older adults' health, highlighting the importance of appropriate post-discharge patient care services during the care transition period from the hospital to their homes or a nursing facility. This study aimed to investigate older adults’ need for transitional care services (TCS) and identify the associated factors. A 1:1 phone survey was conducted on 300 older adults aged ≥65 years who resided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The results of this study were consistent with those of previous studies. Dronina et al 28 investigated the need for TCS in older adults and reported that the need for “information on social welfare services/resources available in an area in proximity to the patient’s place of living” was high. As a result of examining the need for financial assistance for older women with liver cancer, 29 patients exhibited a high need (72.2%) for support of connection to community resources through the in-hospital social services team.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study were consistent with those of previous studies. Dronina et al 28 investigated the need for TCS in older adults and reported that the need for “information on social welfare services/resources available in an area in proximity to the patient’s place of living” was high. As a result of examining the need for financial assistance for older women with liver cancer, 29 patients exhibited a high need (72.2%) for support of connection to community resources through the in-hospital social services team.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study that identified the difficulties experienced by patients in the process of moving to long-term care institutions or elderly living facilities after being discharged from the hospital, the unmet needs of elderly patients, especially at the time of discharge, are related to the diagnosis and treatment plan. Training and information for self-management after discharge and information on social welfare services available near the residence were provided [13][14][15].…”
Section: Introductionmentioning
confidence: 99%